Animal aggregations promote emergent aquatic plant production at the aquatic–terrestrial interface. Issue 10 (19th August 2020) - Lopez, Jonathan W.; Parr, Thomas B.; Allen, Daniel C.; Vaughn, Caryn C.
Abstract: The roles mobile animals and abiotic processes play as vectors for resource transfers between ecosystems ("subsidies") are well studied, but the idea that resources from animals with limited mobility may be transported across boundaries through intermediate taxa remains unexplored. Aquatic plants ("macrophytes") are globally distributed and may mediate transfers of aquatic‐derived nutrients from aggregations of aquatic animals to terrestrial ecosystems when consumed by terrestrial herbivores. We used mesocosms (94 × 44 cm) to test whether aquatic animal‐generated biogeochemical hotspots increase growth and nutrient content in macrophytes using the macrophyte Justicia americana and freshwater mussels. Justicia americana biomass production increased and belowground biomass allocation changed with increasing mussel density. At high mussel density, water‐column phosphorus increased and carbon:phosphorus ratios in J. americana tissues decreased. We deployed motion‐sensing cameras to explore herbivory on J. americana growing along the margins of the Kiamichi River, Oklahoma, and documented feeding by large mammals ( Odocoileus virginianus, Sus scrofa, and Bos taurus ). Thus, biogeochemical hotspots generated by aquatic animal aggregations can promote macrophyte production that subsequently is transferred to terrestrial animals. More broadly, this suggests that reductions in aquatic animal biomass may have bottom‐up impacts that indirectly affect terrestrial ecosystems via plant–animal interactions bridging ecosystem boundaries.